2009
DOI: 10.1002/bies.200900063
|View full text |Cite
|
Sign up to set email alerts
|

Emerging mechanisms in morphogen‐mediated axon guidance

Abstract: Early in animal development, gradients of secreted morphogenic molecules, such as Sonic hedgehog (Shh), Wnt and TGFbeta/Bmp family members, regulate cell proliferation and determine the fate and phenotype of the target cells by activating well-characterized signalling pathways, which ultimately control gene transcription. Shh, Wnt and TGFbeta/Bmp signalling also play an important and evolutionary conserved role in neural circuit assembly. They regulate neuronal polarization, axon and dendrite development and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
65
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 114 publications
0
65
0
Order By: Relevance
“…Shh signaling appears to regulate not only neural progenitor cell division but also cell fate specification and neuronal maturation (27), suggesting that the APP/AICD-dependent derangement of the Shh pathway in the DS brain may underlie, in addition to proliferation impairment, defective cell fate specification and neuronal maturation. Moreover, increased levels of the sAPP fragment may also contribute to derangement of these processes (20) in the DS brain.…”
Section: Down Syndrome (Ds)mentioning
confidence: 99%
“…Shh signaling appears to regulate not only neural progenitor cell division but also cell fate specification and neuronal maturation (27), suggesting that the APP/AICD-dependent derangement of the Shh pathway in the DS brain may underlie, in addition to proliferation impairment, defective cell fate specification and neuronal maturation. Moreover, increased levels of the sAPP fragment may also contribute to derangement of these processes (20) in the DS brain.…”
Section: Down Syndrome (Ds)mentioning
confidence: 99%
“…Wnt signaling stimulates axonal remodeling, pathfinding, dendritic arborization, and neuronal connectivity in the central nervous system (5-7). Many Wnt signaling components have been implicated in neurite outgrowth (7)(8)(9). For instance, Wnt7b induces dendritic morphogenesis in mouse hippocampal neurons via a noncanonical pathway including Dvl, Rac, and JNK (10).…”
mentioning
confidence: 99%
“…Although interaction among these proteins might be important for efficient Shh reception [13], it is well established that Shh binding to Ptch activates signal transduction in Shhreceiving cells. In basal conditions, Ptch inhibits Smo, but upon ligand binding, this inhibition is released and Smo activates a cascade that leads to control of gene transcription and likely to the activation of local second messengers in growth cones [14]. Song et al [7] observed that Ptch and Smo localized at the surface of serotoninergic caudal raphe axons as they descend along the spinal cord and demonstrated that Ptch and Smo function is required for multidirectional Shh repellent activity.…”
mentioning
confidence: 99%
“…Multidirectional guidance by a single signal also raises the perhaps general question of how each individual axon senses the absolute concentration of a given guidance cue and interprets it accordingly. An important contributing factor might be the type and level of surface receptors present in each growth cone [14]. As mentioned above, Shh reception involves different transmembrane proteins that appear to interact with Ptch [13], even though it is unclear whether and how this interaction modifies signal transduction.…”
mentioning
confidence: 99%
See 1 more Smart Citation